HIBISCUS SABDARIFFA LINN. MENCEGAH PENURUNAN FUNGSI MEMORI KERJA PADA MENCIT MODEL DIABETES TIPE 2 - Anggraeni, Risa Kusuma; Andraini, Trinovita (E-Jurnal Medika Udayana, 2022)
Diabetes mellitus (DM) is a risk factor for memory impairment. Administration of herbal medicine which is rich in polyphenol has been believed have a positive impact on memory performance.  Recent studies showed one of the potential candidates of herbal medicine is Hibiscus sabdariffa Linn. (HSL) which can improve memory function in several conditions. However, researches which prove will HSL affect memory function in DM is still limited. The aim of the study is to investigate the effect of HSL administrating on spatial working memory in DM. This study is an experimental study using DDY mice aged 9-11 weeks which were divided into four groups: control (K), DM control (DM), DM with HSL at a dose of 200 mg/kgBW (DM-HSL200), and DM with HSL at a dose of 400 mg/kgBW (DM-HSL400). Experimental animals were given treatment for 28 days. All groups performed Y- Maze spontaneous alternation before and after treatment. The results of this study showed a decrease in memory function in the DM group. Administration of HSL can maintain memory function in DM mice. These findings indicate that administration of HSL has potency to prevent memory impairment in DM. Keywords : Hibiscus sabdariffa Linn., spatial working memory, diabetes mellitus, Y-maze spontaneous alternation.